Digital Learning and Vision Health: Exploring Post-Pandemic Refractive Error Trends Among Students in Tripura - Datta, Goutam (Journal of Neonatal Surgery, 2025)
The rapid transition to digital learning during and after the COVID-19 pandemic has significantly altered students’ visual environments, raising concerns about emerging trends in refractive errors. This qualitative study explores the perceptions, experiences, and awareness of students in Tripura regarding vision health in the context of increased screen exposure. Using a phenomenological approach, data were collected through semi-structured interviews and focus group discussions with school and college students. The study examines behavioral patterns such as prolonged screen time, reduced outdoor activities, and inadequate eye care practices, and how these factors contribute to symptoms associated with refractive errors, including eye strain, blurred vision, and headaches. The findings reveal a growing self-reported incidence of visual discomfort and possible refractive changes, alongside limited awareness about preventive measures and eye health management. Participants also highlighted challenges related to digital device dependency, academic pressure, and lack of institutional guidance on safe screen use. The study underscores the need for integrated awareness programs, regular vision screening, and policy interventions in educational settings to mitigate the adverse effects of digital learning on vision health. By providing in-depth insights into student experiences, this research contributes to the broader discourse on public health and education in the post-pandemic era.